(untitled) (Revista Kriterion, 2025)
This article sought to provide a new interpretation of Adam Smith’s view about moral luck. In his work Theory of Moral Sentiments, Smith diagnosed the influence of luck on our moral sentiments, he named this phenomenon by “irregularity of sentiments”. Given the proximity between Smith’s analysis of this irregularity of sentiments and the debate on moral luck, some philosophers have attempted to shed more light on his position on moral luck. I defend that these previous interpretations fail to notice the real connection between the virtue of justice and the irregularity of moral sentiments. As I intend to argue, this connection gives us the proper tools to better understand Smith’s position in the debate.